Potensi Konflik Tenurial di Desa Bontoala dan Desa Taeng, Kabupaten Gowa: Motivasi Masyarakat dalam Pemanfaatan Tanah Negara pada Sempadan Sungai Jeneberang - Isra Nurdin; Sukirman Rahim; Iswan Dunggio (Badan Penerbitan Fakultas Pertanian (BPFP), Universitas Bengkulu, 2025)
Use of state-owned land along river setbacks is a common phenomenon in densely populated urban areas. This study analyzes how communities utilize state land on the banks of the Jeneberang River and their motivations for settling there, which may trigger tenurial conflicts. The research was conducted in Bontoala and Taeng Villages, Pallangga Subdistrict, Gowa Regency, South Sulawesi, using a qualitative approach with in-depth interviews, field observations, and document review. Findings show that residents use the riparian zone for housing, small-scale enterprises (scrap collection, kiosks, livestock), and everyday social activities. The main motivations to reside in the area are economic factors (access to low-cost/abandoned land), locational advantages (proximity to Makassar and strategic for livelihoods), and socio-cultural factors (family inheritance, traditions, and community ties). However, this illegal use has implications for environmental degradation, declining river quality, and the emergence of potential horizontal and vertical conflicts over land tenure legality. The study underscores the need for regulatory measures and sustained public outreach to prevent conflict escalation in river setback areas.